Primary malignant melanoma at esophagogastric junction - Elkiran, Emin Tamer; Çelebi, Selman; Aygen, Bilge; Karao?lu, Aziz; Özercan, Ibrahim (My University, 2006)
A 63-year-old-man was admitted to the hospital with two months history of abdominal pain, anorexia and weight loss. The endoscopy demonstrated a 2 cm in size, dark blue, pediculated and polypoid tumor almost under the esophagogastric junction with a diagnosis of primary malignant melanoma of the esophagus (PMME). Patient died of progression of liver metastases 2 months after the diagnosis. Clinical and biological caharacteristics of this rare tumor with its management oppurtinities are also reviewed in the light of pertinent literature.
Keywords: Chemotherapy; Esophagus; Malignant melanoma